2013
DOI: 10.1002/ppul.22798
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Doripenem in Pediatric Cystic Fibrosis Patients in Case of Meropenem Shortages

Abstract: Ceftazidime is the only anti-pseudomonal beta-lactam that has been reported to be administered by extended infusion in pediatric cystic fibrosis (CF) patients. A small pediatric pharmacokinetic/pharmacodynamic study has been published regarding the use of intermittent extended infusion doripenem in the treatment of an acute pulmonary exacerbation (APE) in pediatric CF patients; however, clinical use of intermittent extended infusion doripenem in pediatric CF patients has not been previously reported. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…doripenem replaced meropenem in the therapy of pediatric patients with cystic fibrosis [12]. This strategy cannot be 100% applied to neonatal care, since possible alternatives may not have been studied in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…doripenem replaced meropenem in the therapy of pediatric patients with cystic fibrosis [12]. This strategy cannot be 100% applied to neonatal care, since possible alternatives may not have been studied in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent extended infusion of doripenem was successfully used in a patient with history of methicillin-sensitive S. aureus, S. maltophilia, Pseudomonas stutzeri , and B. cenocepacia infections and showing meropenem shortage ( Zobell et al, 2014 ). The report demonstrated that it is possible to administer doripenem also in children and that its intermittent extended infusion is effective to improve pulmonary function.…”
Section: New Therapies and Approaches To Overcome B Cenocementioning
confidence: 99%
“…Patients received between 75 and 90 mg/kg/day of the drug in 3 divided doses utilizing an infusion of 1 hour. Possible adverse reactions to the drug were mild in nature and did not require discontinuation [Zobell et al 2014].…”
Section: Characteristic Resultsmentioning
confidence: 99%